Tools for Developing Applications in the Semantic Web of Things: A Systematic Literature Review - Galindo-Semanate, Manuel; Niño-Zambrano, Miguel (Revista Facultad de Ingeniería, 2024)
The Internet of Things (IoT) has revolutionized various sectors. Despite several years since its inception, developing interoperable smart object environments remains challenging due to hardware and software heterogeneity and the difficulty in applying formal software development methods to ensure quality. The Semantic Web of Things (SWoT), combined with a set of best software development practices, presents a promising solution to ease the development of semantically interoperable IoT environments. This paper conducted a systematic review of tools for SWoT application development to establish the best decisions for developing these environments, while also seeking a proper balance to manage heterogeneity and quality. The findings highlight best practices, emerging trends, and future opportunities in SWoT development. Key trends, approaches, and tools used in SWoT application development were identified. Additionally, it is confirmed that the adoption of international standards and the use of semantic technologies are crucial to overcoming interoperability and quality challenges in IoT applications.